FINANCIAL FEASIBILITY ANALYSIS OF PARASITIASIS CALVES TREATMENT ON CATTLE BREEDING OF SMALLHOLDER IN MAGELANG REGENCY CENTRAL JAVA PROVINCE - Purwaningsih Purwaningsih; Tri Anggraeni Kusumastuti; Bambang Sumiarto (Buletin Peternakan, 2017)
This research was aimed to identify the financial feasibility of parasitiasis treatment for calves in the small holder breeding farm in Piji Subdistrict, Podosoko Village, Magelang Regency. Farmer was taken purposively, considering their objective of keeping cattle (breeding). Eight calves naturally infected gastrointestinal parasites were selected based on consideration of the uniformity of the age (4 months) breeds of Limousin-PO (LimPO) male 120-125 kg of body weight. They were divided into two groups, consisting of four calves for each group (Group I without treatment and Group II with improved health management). Farmers income was calculated based on the input and output data gathered from interview. The data were compared between Group I and II. Result showed that the value of additional revenue of the calves was IDR 4,230,000 and the selling price of one head of the treated antiparasitic calf was IDR 6,047,000. The calves net benefit in Group II was IDR 142,661/head/year, while group with improved health management (Group II) achieved the net income of IDR 283,621/head/year.